Nutritional Knowledge and Behavior of Adults: Their Relations with Sociodemographic Factors - HAKLI, Gulperi; ASIL, Esma; UCAR, Asli; OZDOGAN, Yahya; YILMAZ, Mustafa Volkan; OZCELIK, Ayse Ozfer; SURUCUOGLU, Metin Saip; CAKIROGLU, Funda Pinar; AKAN, Lale S. (Pakistan Journal of Nutrition, 2016)
This cross-sectional study was carried out for the purpose of investigating the factors affecting nutritional knowledge and behaviors of adults and the relation between nutritional knowledge and these behaviors. The study population consisted of 1062 adults aged 18-65 who presented to health care centers (mean age was 37.6±11.7 years). Data was collected through a questionnaire. In both score types, participants with undergraduate and graduate degrees and the employed got the highest scores. The difference between the mean knowledge score according to age (p<0.05) and educational status (p<0.01) was significant. The difference in the mean knowledge score on educational status resulted from the gap between those who were illiterate and who received university education and higher education, for the age group of 18-29 year old. With respect to behavioral scores, the differences between gender, marital status, age, employment status and educational status were significant (p<0.01). The group that caused the difference in marital status was the single ones, in the age groups of 18-29 years and >50 year old and the difference in educational status resulted from the illiterate and from those with university degrees and higher education. It was also found that there was a significant positive relationship between the nutritional knowledge score and the behavior score (r = 0.248, p<0.01). The results of the study revealed that the more adults’ ages and educational status increased, the more nutritional knowledge level they had; also gender, age, educational status, employment status and marital status affected adults’ positive nutritional behaviors.